Differentiated Instruction in Mathematics Education: A Systematic Literature Review - Maryani, Dwi; ‎ , Mardiyana; ‎ , Riyadi (KnE Social Sciences, 2025)
This study aims to examine scientific journals by collecting reliable sources related to differentiated instruction in mathematics education. Differentiated instruction is a teaching approach that recognizes the diversity of students’ learning based on their abilities and interests. The method used to write this article is a literature review. The approach used to analyze journal articles is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The research began by searching for articles related to the topic to be investigated through Scopus, ERIC, and Proquest databases. The criteria for scientific articles used as information are those from international journals updated in the last 5 years, from 2018 to 2023. The analysis of 11 scientific articles shows that research has been conducted worldwide. The subjects in differentiated instruction research consist of students, teachers, and pre-service teachers. Most of the studies use qualitative research methods and aim to improve the understanding, development, and implementation of differentiated instruction practices in mathematics education.